Volatile biomarkers for early-stage detection of insect-infested brown rice: Isopentenols and polysulfides. (15th January 2020) - Tanaka, Fukuyo; Magariyama, Yukio; Miyanoshita, Akihiro
Highlights: Investigation of volatile biomarkers to detect insects in stored brown rice. Non-target analysis of volatiles with TD–GC–MS was performed. Isopentenols (prenol & isoprenol) were the biomarkers associated with moths. Polysulfides (e.g., dimethyl trisulfide) were associated with S. zeamais damage. Abstract: To reduce food loss from stored products by insect attack, monitoring and early detection of insects are essential. Presently, monitoring with pheromone traps is the primary method for detection; however, traps are effective only after the insects propagate. Detection and identification of the early volatile biomarkers arising from insect-infested brown rice was performed in this study to develop an alternative detection strategy. Brown rice was infested with eggs of seven insect species, including Sitophilus zeamais and Plodia interpunctella . Infested rice emitted at least one of the volatile compounds prenol, isoprenol, dimethyl disulfide, and dimethyl trisulfide (DMTS). In particular, isopentenols were generated by moths within one week of infestation, whereas they were not released from non-infested rice . DMTS was detected from all insect-infested brown rice, especially S. zeamais and P. interpunctella . These volatiles are potential early biomarkers for the presence of insects in brown rice.